Towards developing distributed heterogeneous mobile phone applications - Kattan, Ali R. Mustafa; Abdullah, Rosni; Abdul Salam, Rosalina; Ramadass, Sureswaran (2009)
The advances in the mobile phone technology have enabled such devices to be programmed to run general-purpose applications using a special mobile edition of the Java programming language.Java is designed to be a heterogeneous programming language targeting different platforms.Such ability when coupled with the provision of high-speed mobile Internet access would open the door for a new breed of distributed mobile applications.This paper explores the limitations of this technology and addresses the consideration that must be taken when designing and developing such applications.